The promotion of sestrin2/AMPK signaling by HIF-1α overexpression enhances the damage caused by acute myocardial infarction - Jie Wang; Honglei Du; Qing Sun; Weiping Wan; Haifeng Zhang (BMC Cardiovascular Disorders, 2023)
Abstract Objective Acute myocardial infarction (AMI), is a serious form of coronary heart disease. The present study sought to investigate the impact of HIF-1α on AMI, along with its fundamental mechanism. Methods Sprague-Dawley (SD) rats were used to conduct an AMI model. 2,3,5-triphenyl-2H-tetrazolium chloride (TTC) staining was used examine the region of myocardial infract area at various time intervals. Protein expression levels were detected using western blotting. The rats were randomly divided into sham, model, negative control (NC), HIF-1α overexpression (HIF-1α-OE), and HIF-1α-OE+ si-sestrin2 groups. We examined the impact of HIF-1α overexpression on AMI rats using Haematoxylin-Eosin (H&E) staining, TTC staining, enzyme-linked immunosorbent assay (ELISA), TdT-mediated dUTP Nick-End Labeling (TUNEL) assay, and immunohistochemistry (IHC) staining. Results According to the TTC findings, the region affected by myocardial infarction reached its peak at day 14. Based on the results from the western blot analysis, the levels of HIF-1α and sestrin2 were found the minimum on day 28. Subsequently, we discovered that the overexpression of HIF-1α rescued the cardiac function parameters, improved the morphology of myocardial tissue, and mitigated inflammation. Furthermore, the overexpression of HIF-1α led to a reduction in the levels of MDA and an increase in the levels of SOD. Moreover, the overexpression of HIF-1α resulted in a decrease in cellular apoptosis. This result was confirmed by the expression levels of Bcl-2 and Bax. Nevertheless, the defensive impact of elevated HIF-1α expression was somewhat counteracted by the suppression of sestrin2. In terms of mechanism, the overexpression of HIF-1α enhanced the levels of sestrin2 and the protein adenosine monophosphate activated kinase (AMPK). Conclusion Our research suggests that the overexpression of HIF-1α may rescue the damage to myocardial tissue, and this effect is associated with the sestrin2/AMPK signaling pathway. Our study provides a novel comprehension of the protective effects of HIF-1α overexpression on AMI.